2015
DOI: 10.1038/jid.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Synthase 4 Regulates Stem Cell Homeostasis and Hair Follicle Cycling

Abstract: Ceramides are crucial for skin barrier function, but little is known about the regulation of epidermal appendages and whether stem cell populations that control their regeneration depend on specific ceramide species. Here we demonstrate that ceramide synthase 4 (CerS4) is highly expressed in the epidermis of adult mice where it is localized in the interfollicular epidermis and defined populations within the pilosebaceous unit. Inactivation of CerS4 in mice resulted in precocious activation of hair follicle bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…In the context of cancer, we observed that this increased ciliary TGF-β signaling and Shh activation enabled by the loss of CerS4 and long-chain ceramides in tumor cells promoted metastatic progression in mice. Our observations of alopecia and skin abnormalities in CerS4 −/− mice are consistent with other studies (46, 47), which link increased epidermal TβRI abundance with alopecia (48). Elsewhere, loss of Patched2 (Ptch2), a receptor protein that inhibits Shh signaling, has been associated with alopecia in Ptch2-deficient mice (63).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the context of cancer, we observed that this increased ciliary TGF-β signaling and Shh activation enabled by the loss of CerS4 and long-chain ceramides in tumor cells promoted metastatic progression in mice. Our observations of alopecia and skin abnormalities in CerS4 −/− mice are consistent with other studies (46, 47), which link increased epidermal TβRI abundance with alopecia (48). Elsewhere, loss of Patched2 (Ptch2), a receptor protein that inhibits Shh signaling, has been associated with alopecia in Ptch2-deficient mice (63).…”
Section: Discussionsupporting
confidence: 93%
“…The genetic loss of CerS4 resulted in irreversible alopecia, which was concomitant with alterations in sebaceous glands and sebum contents in adult CerS4 −/− compared to wild-type CerS4 +/+ mice (fig. S3D), as previously reported (46, 47). …”
Section: Resultssupporting
confidence: 84%
“…CerS3- Significance was determined by Student's t test. *P < 0.05, **P < 0.01, ***P < 0.001. generated ultra-long sphingolipids play key roles in the homeostasis of skin barrier function (34), whereas deficiency of CerS4 is associated with skin disorders such as irreversible alopecia (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that CerS1 deficiency in mice causes progressive Purkinje cell loss and cerebellar shrinkage (Ginkel et al, 2012), CerS2-deficient mice suffer from hepatocarcinogenesis (Imgrund et al, 2009;Pewzner-Jung et al, 2010), myelin degeneration and microglia activation (Imgrund et al, 2009;Ben-David et al, 2011), and CerS4-deficient mice show progressive hair loss (Ebel et al, 2014;Peters et al, 2015). In CerS-deficient mice, the ceramide species for which the respective CerS is specific and the corresponding sphingolipid derivatives are strongly decreased.…”
Section: Introductionmentioning
confidence: 99%